2020
DOI: 10.1021/acsaem.0c02360
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Carbon Surfaces Tunes the Redox Stability of Polyoxometalate@Carbon Electrodes

Abstract: The use of redox-active polyoxometalates (POMs) offers unique opportunities for the development of advanced functional materials, but the use of such systems is often limited by their instability in operando. To enhance the functional stability of POMs they are often immobilized onto solid supports, though complex POM-hybridization strategies are usually required. Herein we describe a simple and scalable method for the fabrication of POM-based redox materials. Our method involves functionalizing inexpensive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This is an important drawback for the development of electrodes based exclusively on POMs. This is why most electrodes used for (photo)-(electro)-catalysis required the use of conductive additives (e.g., carbon black) . So far, only few investigations have been engaged to study the electron-transport properties in the solid state and to improve their electrical conductivity.…”
Section: Poms As Electrocatalytically Active Multiredox Centersmentioning
confidence: 99%
“…This is an important drawback for the development of electrodes based exclusively on POMs. This is why most electrodes used for (photo)-(electro)-catalysis required the use of conductive additives (e.g., carbon black) . So far, only few investigations have been engaged to study the electron-transport properties in the solid state and to improve their electrical conductivity.…”
Section: Poms As Electrocatalytically Active Multiredox Centersmentioning
confidence: 99%
“…This method confirms both that: (a) the micellar species spontaneously and rapidly adhere to the GC surface in the presence of acid, and; (b) the micelles are not electrodeposited but rather, chemically adsorbed to the surface. The importance of acid in the deposition process suggests that H 2 SO 4 is either promoting surface oxidation of the carbon in order to produce functional groups which facilitate favourable non-covalent interactions between {W 17 C 20 } and the GC surface (a phenomenon recently observed in POM-activated carbon composites), 22 or that the protons otherwise act as bridging agents between the carbon and metal-oxide surfaces to facilitate deposition. We discuss these hypotheses in more detail below.…”
Section: Electrochemical Analysismentioning
confidence: 99%
“…18,19 Similarly, the deposition of POMs onto electrode materials has been achieved through non-covalent strategies including electrostatic interactions, 20 π-π interactions, 21 and oxidation of electrode surfaces to promote weak interactions. 22 A particular advantage offered by hybrid POMs is their capacity to act as amphiphiles and form ordered superstructures such as micelles and vesicles in solution. [23][24][25] Recent work in our group has demonstrated that the redox properties of molecular hybrid POMs are translated to solution-phase supramolecular assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Carbon materials are widely utilized as sacrificial templates to assemble porous materials on account of convenient acquisition, regular morphology and easy removal. [27][28][29] In this procedure, carbon sphere precursors could be obtained via hydrothermal treatment of glucose, which could be decomposed under high temperature annealing.…”
Section: Introductionmentioning
confidence: 99%